Retrospective analysis of outcomes in the programme of fast-tracking of antiretroviral therapy for patients admitted to a palliative care centre after diagnosis of opportunistic infections - Edwin, Christina (Department of Public Health and Family Medicine, 2014)
Includes bibliographical references (leaves 60-64).